Prognostic value of micro-RNA 375, 133, 143, 145 in esophageal carcinoma: A systematic review and meta-analysis - Fang, Pinhao; Zhou, Jianfeng; Li, Xiaokun; Luan, Siyuan; Xiao, Xin; Shang, Qixin; Zhang, Hanlu; Yang, Yushang; Zeng, Xiaoxi; Yuan, Yong (Frontiers in Oncology, 2022)
Many studies have confirmed that micro-RNA (mir) is related to the prognosis of esophageal carcinoma (EC), suggesting the mir could be used to guide the therapeutic strategy of EC. Some of mir molecules are considered as favorable prognostic factors for EC. The purpose of our study is to evaluate the prognostic potential of mir-375, 133, 143, 145 in primary EC, we summarized all the results from available studies, aiming delineating the prognostic role of mir in EC. Relevant studies were identified by searching databases including Medline, Embase, Web of science, Cochrane Library. The studies which explored the prognostic value of mir-375, 133, 143, 145 expressions on survival outcomes in patients with EC were included in this study. The hazard ratios (HR) and their responding 95% confidence interval were also extracted. A total of 25 studies were collected, including 1260 patients, and the prognostic values of four mirs in EC were analyzed. Survival outcomes including overall survival (OS), progression-free survival (PFS) and disease-free survival (DFS) were used as the primary endpoint to evaluate the prognostic value of mir. The pooled analysis results showed that up-regulation of mir-375 indicated favorable OS (HR=0.50; 95%CI: 0.37-0.69; P<0.05). In addition, the up-regulation of mir-133, 143 and 145 (HR=0.40, 95%CI: 0.24-0.65, P<0.001; HR=0.40, 95%CI: 0.21-0.76, P < 0.001; HR=0.55, 95%CI: 0.34-0.90, P<0.001) are also proved as protected factors in EC. Therefore, our study demonstrated that these mirs may have the potential to be used as prognostic biomarkers for EC in clinical practice.